The Gradual Correction of Rigid Pes Cavus Using Midfoot Osteotomy Combined with Ilizarov Methods - Yaxing Li; Boquan Qin; Jia Li; Shijiu Yin; Yi Ren; Ye Wu; Xiang Fang; Huiqi Xie; Hui Zhang (Orthopaedic Surgery)
Objective Midfoot osteotomy combined with Ilizarov methods of correction is a rarely reported treatment that is particularly well‐suited for severe rigid pes cavus. The study aimed to assess the radiological and clinical results of patients who had been treated for rigid pes cavus using this method. Methods The study retrospectively analyzed the clinical and radiological data of 15 pes cavus in 12 patients who were corrected by midfoot osteotomy with Ilizarov external frame in our department from March 2020 to September 2022. Radiologic outcomes were measured using the Meary angle (MA), talus‐first metatarsal angle (TM1A), calcaneal varus angle (CVA) and foot length with weight‐bearing radiographs. Functional assessments were evaluated in terms of pain, function, and quality of life by using the visual analogue scale (VAS), the American Orthopedic Foot and Ankle Society hindfoot scale score (AOFAS), and 36‐item Short Form Health Survey (SF‐36). Additionally, the postoperative satisfaction of patients was investigated by a questionnaire. The clinical and radiological results were evaluated by a paired t‐test. Results All patients received plantigrade feet and pain relief. The mean follow‐up was 33.1 ± 5.0 months (range from 25 to 41 months). The etiology included poliomyelitis (4), idiopathic (3), trauma (2), spina bifida (2) and tethered cord syndrome (1). The duration of gradual correction was 30.4 ± 10.6 days, and the external fixation time was 116.3 ± 33.3 days. The bony union rate was 100%. The VAS, AOFAS, and SF‐36 scores significantly improved (p < 0.05). The MA, TM1A, and CVA were close to or reached the normal range postoperative (p < 0.01). The length of each foot was well preserved, which was increased more than 0.8 cm than preoperative. No major complications were reported except two cases of mildly hindfoot varus deformity. The results of the questionnaire showed that patients' satisfaction was 92% (11/12). Conclusion Midfoot osteotomy combined with Ilizarov external frame proved to be a reasonable procedure with satisfying mid‐term results for the gradual correction of rigid pes cavus.